The Learning Thermometer: Closing the loop between teaching, learning, wellbeing and support in universities - Stallman, Helen; King, Sharron (Journal of University Teaching and Learning Practice, 2016)
The increasing awareness and impact of mental health problems in university students in addition to a need for objective measures of teaching quality provide the impetus for a new approach to supporting students. There is a need for more effective tools that integrate the institutional silos of teaching, learning, support, and wellbeing to help students maximise their educational outcomes. This paper provides an overview of an innovative student-centred tool, The Learning Thermometer, as an efficient and effective way to integrate the institutional silos and embedding student support within the mainstream curriculum. The Learning Thermometer comprises four web-based surveys that are completed by students during the semester. After each survey students are provided with relevant feedback, and if necessary, suggestions of strategies, resources and people who can help them with their learning and/or wellbeing. The Learning Thermometer has the potential to ensure every student has access to support, if and when they need it during their studies. Recommendations are made on how the tool can be used to enhance teaching, learning and student health and wellbeing.